Analisis Kejahatan Narkotika dengan Perspektif the Economic of Crime - Gurbacov Gurbacov; Iqrak Sulhin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to provide an understanding of the analysis of narcotics crime from the perspective of the economic of crime from the perpetrators point of view and to provide suggestions on how to model the prosecution of narcotics criminals from the perspective of the economic of crime. The problem is focused on the perspective of the perpetrator against the consideration of costs and benefits in narcotics crimes. To approach this problem, references are used, namely the rational choice theory from Becker, the deterrence theory from Beccaria, and the principle of utilitarianism from Bentham. The data were collected through library research and field studies, namely interviews and analyzed qualitatively. The results of the study state that the market situation for methamphetamine in Central Java Province provides benefits to perpetrators, with small capital generating large profits. Actors are not exposed to market risk but legal risk. Therefore, the distribution is carried out in small packages and the sales system is in a mineed or addressed mode so that it is safe and disconnected. This study concludes that the perpetrators have assessed the costs and benefits so that the model for overcoming narcotics crime from the perspective of the economic of crime which is analyzed with consideration of costs and benefits from the perspective of the perpetrators in committing crimes in the jurisdiction of Central Java is carried out in two ways, namely repressive and preventive.